2006
DOI: 10.1093/chemse/bjl015
|View full text |Cite
|
Sign up to set email alerts
|

The Sleep-Enhancing Effect of Valerian Inhalation and Sleep-Shortening Effect of Lemon Inhalation

Abstract: We examined the effects of odorant inhalation on the sleep-wake states in rats. Odorants used in the experiment were clove, jasmine, lavender, lemon, peppermint, pine, rose, sandalwood, valerian, and ylang-ylang. Valerian and rose inhalation significantly prolonged the pentobarbital-induced sleeping time, whereas lemon inhalation significantly shortened it. The effect of valerian inhalation was markedly noticeable. In the anosmic rats, a significant effect of odorants on the pentobarbital sleep time was not se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 33 publications
1
24
0
4
Order By: Relevance
“…Valerian preparations are widely used as herbal tranquillizers whose sedative activity is said to arise from sesquiterpene derivatives such as valerenic acid [8]. This mechanism is supported by results of experiments using spikenard oil [2]. Valerena-4,7(11)-diene was first isolated from valerian, and the same compound was found in spikenard as an active component in the present study.…”
Section: Comparison Of Effects Of Valerena-47(11)-diene With Valerensupporting
confidence: 78%
See 1 more Smart Citation
“…Valerian preparations are widely used as herbal tranquillizers whose sedative activity is said to arise from sesquiterpene derivatives such as valerenic acid [8]. This mechanism is supported by results of experiments using spikenard oil [2]. Valerena-4,7(11)-diene was first isolated from valerian, and the same compound was found in spikenard as an active component in the present study.…”
Section: Comparison Of Effects Of Valerena-47(11)-diene With Valerensupporting
confidence: 78%
“…More in-depth functional analyses of olfactory receptors may in the future clarify the molecular mechanisms related to odor recognition, from receptor binding to higher information processing in the brain. Komori et al examined the effects of odorant inhalation on sleep-wake status in rats [2] and found that valerian oil sedated the autonomic nervous system and that lemon oil activated it; inhalation of valerian oil remarkably prolonged the pentobarbital-induced sleeping time (46% prolongation), whereas that of lemon oil significantly shortened it (22% shortening).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent human study demonstrated that cedrol directly inhaled through the lower airway, but not introduced to the upper airway, causes a suppression of sympathetic outflow and an increase in parasympathetic outflow [31]. The results of various studies on other scents, such as lavender, lemon, valerian, and others, showed considerable agreement with respect to the fact that the effectiveness of odors in prolonging pentobarbital sleep time [32,33], lowering Environ Health Prev Med (2010) 15:27-37 31 blood pressure [34], and suppressing renal sympathetic nerve activity [34] disappeared in anosmic mice or rats, thus indicating the mediation of the olfactory system in the whole process. The authors consider that odors affect human physiology mainly through the olfactory processing pathway; however, in the case of laboratory experiments, the possibility that odorous compounds act directly via the blood-borne pathway could not be eliminated since the concentration of inhaled compounds is relatively high.…”
Section: Olfactory Stimulationmentioning
confidence: 91%
“…L'inhalation de vapeur d'HE de valériane augmente le sommeil induit par le pentobarbital de 46% cela s'accompagne d'une réduction de 39% de l'activité de la GABA transaminase. Le même traitement n'a pas d'effet chez les animaux anosmiques [43]. Ceci permet de supposer que l'olfaction est mise en jeu pour que l'inhalation d'HE agisse sur le SNC.…”
Section: Inhalation Et Olfactionunclassified
“…Les récepteurs olfactifs sont en relation avec les structures du SNC par des projections du bulbe sur le néocortex qui intervient dans la reconnaissance olfactive. Les relations existent aussi entre récepteurs olfactifs et le système limbique, siège de l'émotion et de l'affect [43,44]. …”
Section: Inhalation Et Olfactionunclassified